The systematics of Hypodontium - Manyanga, Phelex (Department of Biological Sciences, 2023)
Hypodontium is a moss genus currently comprising two species, H. dregei and H. pomiforme, endemic to Southern Africa, occurring in Zimbabwe and the eastern and southern parts of the Flora of Southern Africa areas. lt was originally assigned to the family Calymperaceae but was recently moved to Pottiaceae. The two families do not differ absolutely and Hypodontium possesses combinations of characters that could place it in either. This study used molecular DNA sequence data from two chloroplast gene regions, tmLtmF and rps4, to investigate the family status of the genus. The results obtained showed that it is not a member of either Calymperaceae or Pottiaceae, and supports the erection of a new family to accommodate Hypodontium. Hypodontium pomiforme occurs as two distinct morphological forms, and it has been suggested that these two forms might constitute two separate species. This study used both morphological (cluster analysis and Canonical Discriminant Functions Analysis) and molecular (nuclear ITS sequences) data to test this hypothesis. Results of both methods support the idea of significant difference between the two forms. Three species are therefore proposed for the genus Hypodontium, with H. humilopapillosum Manyanga & Hedderson described as new. A key is provided for the three species along with brief descriptions and a distribution map for each.